American Health Quackery : Collected Essays of James Harvey Young - Young, James Harvey (Book collections on Project MUSE., 1992)
James Harvey Young, the foremost expert on the history of medical frauds, finds quackery in the 1990s to be more extensive and insidious than in earlier and allegedly more naive eras. The modern quack isn't an outrageous-looking hawker of magic remedies operating from the back of a carnival wagon, but he knows how to use antiregulatory sentiment and ingenious promotional approaches to succeed in a "trade" that is both bizarre and deceitful. In The Toadstool Millionaires and The Medical Messiahs, Young traced the history of health quackery in America from its colonial roots to the late 1960s. This collection of essays discusses more recent health scams and reconsiders earlier ones. Liberally illustrated with examples of advertising for patent medicines and other "alternative therapies," the book links evolving quackery to changing currents in the scientific, cultural, and governmental environment. Young describes varieties of quackery, like frauds related to the teeth, nostrums aimed at children, and cure-all gadgets with such names as Electreat Mechanical Heart. The case of Laetrile illustrates how an alleged vitamin for controlling cancer could be ballyhooed and lobbied into a national mania, half the states passing laws giving the cyanide-containing drug some special status. And AIDS is the most recent example of an illness that, tragically, has panicked some of its victims and members of the general public into putting their hopes in fake cures and preventives. Young discusses the complex question of vulnerability--why people fall victim to health fraud--and considers the difficulties confronting governmental regulators. From the late 1960s to the early 1990s, the annual quackery toll has escalated from two billion to over twenty-five billion dollars. Young helps us discover why.Originally published in 1992.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.